Effect of GnRH or Estradiol Benzoate on Reproductive Traits during a Heatsynch Protocol in Dairy Cows - Mielke, Laís; Rodrigues, Mityelle da Costa Chaves; Lima, Márcio Érpen; Acosta, Diego Andres Velasco; Pino, Francisco Augusto Burkert Del; Corrêa, Marcio Nunes; Halfen, Jéssica; Xavier, Eduardo Gularte; Brauner, Cássio Cassal (Acta Scientiae Veterinariae, 2016)
Background: Milk production of cows is closely correlated with its reproductive efficiency. One of the several factors influencing the dairy efficiency is the decline in fertility of the cows/heifers. Use of hormonal protocol are often used to improve the fertility of the recipients. Several programs are available to inseminate dairy cows, with variation in the use of different types of hormones, time of use and range of duration period, as well as the time of AI. The objective of this study was to evaluate the efficiency of follicular wave emergence induction of estradiol benzoate in comparison to GnRH in a Heatsynch protocol and its influence on reproductive parameters. Materials, Methods & Results: In this study were used primiparous and multiparous Holstein cows (n = 325). Animals were divided randomly into two different treatments according with the hormone used to induce follicular wave emergence (D0). The GnRH group (n = 167), was given 25 mg, while in the EB group (n = 158) was used 2 mg. At same day, were inserted, a controlled internal drug-releasing containing 1.9 g of progesterone CIDR®. On day 7, CIDR was removed and cows were given 25 mg luteinizing hormone followed by an injection of 1 mg Inducer Ovulation at day 8. Cows were then observed for signs of estrus for at least two hours (twice daily at 7 am and 6 pm) for three days following CIDR® removal. Cows detected in estrus were inseminated 12 h later the estrus detection. Pregnancy status was determined by ultrasonography at 30 ± 5 d and 60 ± 5 d after AI. A single technician was responsible for the estrus detection and inseminations. A single technician was responsible for the estrus detection and inseminations. Ultrassonographic examinations with ultrasound, transrectal linear probe of 5 MHz, were performed for the diagnosis of pregnancy at 30 and 60 days after artificial insemination. Binomially distributed data, such as, estrous response, conception rate, pregnancy rate and pregnancy losses, were analyzed by Chi-square test. Pregnancy rates at 30-35 days and 60-65 days as well as pregnancy losses were considered in the model for the effect of parity (primiparous vs. multiparous) and the group of estrus behavior during the Heatsynch protocol. Conception rate was similar between GnRH (36.1%, 57/158) and EB (37.7%, 63/167) treatments. Cows showing estrus signs after CIDR removed were 71.9% in GnRH and 62% in EB group (P = 0.05). Embryonic losses were different (P = 0.03) according to groups of cows showing estrus signals or not. Discussion: Our results demonstrate that conception rates are not affected by using either EB or GnRH at the beginning of the Heatsynch protocol. Therefore, the EB can be an alternative choice to GnRH at Heatsynch beginning. Similar results were found by autor in dairy cows, once it was also observed that there is no difference in conception rate in two TAI protocols using either GnRH or EB. In Heatsynch protocols the increase in estrus detection are a key factor to increase fertility in lactating dairy cows. It can be explained once animals in regular estrous cycle have a palpable corpus luteum and circulating progesterone concentration higher than 1 ng/mL which leads than to enhance pregnancy ratios. The use of BE at the time of CIDR insertion in TAI protocols for dairy cattle proved to be an alternative to GnRH considering conception rates. Therefore, the use of BE at the time of CIDR insertion in a Heatsynch protocol in dairy cattle proved to be an alternative to GnRH which can be an important tool to increase the TAI utilization by farmers. Furthermore, in Heatsynch protocol cows showing estrus have pregnancy rates improved and lower pregnancy losses.